Analysis and Numerical Calculation for Several Basic Characteristics of Coaxial Magnetic Gears Applied in Robots - Yang Hongjing; Hua Hua; Yang Xiangping; Chen Jiaxin (Jixie chuandong)
Due to its natural characteristics, coaxial magnetic gears are still difficult to be directly applied to industrial robots. Some key basic characteristics such as torque density, transmission ratio, null-space, backlash and torsional stiffness, and stable working area are still insufficient. For this reason, this study takes the harmonic gear performance of the national standard type 14 as the reference object, uses the relevant electromagnetic theory and the analogy method to study and compare the related performance of the coaxial magnetic gear with the same space size and its numerical calculation method, stability and the integrated technology of servo motors and coaxial magnetic gears. It is pointed out that the lack of torsional stiffness is the key factor that restricts the use of coaxial magnetic gears in robots, and the research focus of the coaxial magnetic gear servo control for robots in the future is clarified.